Cardiac troponin I reveals diagnostic and prognostic superiority to aminoterminal pro-B-Type Natriuretic Peptide in sepsis and septic shock - Forner, Jan; Schupp, Tobias; Weidner, Kathrin; Rusnak, Jonas; Jawhar, Schanas; Dulatahu, Floriana; Brück, Lea Marie; Behnes, Michael; Hoffmann, Ursula; Bertsch, Thomas; Kittel, Maximilian; Akın, Ibrahim (Journal of Clinical Medicine, 2022)
Data regarding the prognostic value of cardiac biomarkers in patients suffering from sepsis or septic shock is scarce. Studies investigating the prognostic role of cardiac biomarkers in patients with sepsis and septic shock were commonly published prior to the sepsis-3 criteria and were often not restricted to septic patients only, too. This study investigated the diagnostic and prognostic value of the aminoterminal pro-B-type Natriuretic Peptide (NT-pro BNP) and cardiac troponin I (cTNI) in patients with sepsis and septic shock. Consecutive patients with sepsis and septic shock were included from 2019 to 2021. Blood samples were retrieved from the day of disease onset (i.e., day 1), day 2 and 3. Firstly, the diagnostic value of the NT-pro BNP and cTNI to diagnose sepsis or septic shock was tested. Secondly, the prognostic value of the NT-pro BNP and cTNI was examined with regard to the 30-day all-cause mortality. The statistical analyses included univariable t-tests, Spearman’s correlations, C-statistics, Kaplan-Meier analyses and Cox proportional regression analyses. A total of 162 patients were included prospectively, of which 57% had a sepsis and 43% a septic shock. The overall rate of all-cause mortality at 30 days was 53%. With an area under the curve (AUC) of 0.658 on day 1 and 0.885 on day 3, cTNI expressed a better diagnostic value than NT-pro BNP, especially on day 3 (ΔAUCd3 = 0.404; p = 0.022). Furthermore, cTNI displayed a moderate but slightly better prognostic value than NT-pro BNP on all examined days (AUC for cTNI, d1 = 0.635; 95% CI 0.541-0.729; p = 0.007 vs. AUC for NT-pro BNP, d1 = 0.582; 95% CI 0.477-0.687; p = 0.132). In conclusion, cTNI was a reliable diagnostic parameter for the diagnosis of sepsis and septic shock, as well as a reliable prognostic tool with regard to 30-day all-cause mortality in patients suffering from sepsis and septic shock.
Gesehen am 10.07.2023